Positioning WhatsApp and Telegram in Kazakhstan as group phenomenons of the Internet space (Herald of Journalism, 2024)
The article analyzes the modern processes of development of Internet messengers (IM), which are defined as a special type of social network. The purpose of the study is to outline the problems of classification and typologization of new types of media resources based on foreign and domestic experience. Examples of complex studies are given, taking into account the technical and target characteristics of mobile and web applications, as well as the administrative policy of their developers about effective security, encryption and data storage. A comparative analysis of the most widespread Internet messengers and social networks in Kazakhstan and their relationship with traditional media is carried out. The statistics of their use and the outlined trends of evolutionary development allowed to identify patterns of distribution on a regional scale against the background of global trends. Empirical data based on the example of mass media of the Kostanay region are presented, giving an idea of the general orientation of editorial policies in the period of formation of the new Internet infrastructure. Special attention is paid to the communication advantages of the leading Internet messengers WhatsApp and Telegram, and their competition with traditional social networks through the introduction and establishment of new information tools (channels, infobots, communities, private groups, etc.).The scientific novelty of the paper lies in the study and detailed analysis of the distinctive features of the new generation of Internet communicators as opposed to web-oriented traditional social networks, identifying the regularity of the ongoing processes and formulating an innovative approach to studying the nature of WhatsApp and Telegram Internet messengers as personal-oriented applications with a high degree of personalization and protection. From a practical point of view, data on the prevalence of IM used in Kazakhstan in comparison with the world experience is given, and the peculiarities of positioning of these means of communication in the Kazakhstani media environment are revealed.
Keywords: Internet messengers, social networks, WhatsApp and Telegram, Kazakhstan.